Intensitas Supervisi Kepala Sekolah Terhadap Proses Pembelajaran - Limaheluw, Maritje Henderina (Guidance and Counseling Study Program, Pattimura University, 2018)
This is a research of school activity that survey the Civics teachers performance to improve an best optimum learning achievement and school quality that was expected in the curriculum. Method of study is School Actian Research by using descriptive qualitative approach. This research was conducted in three cycles or stages in Civics (PKN) teachers on Christian High School 1Saparua. This study were founding that on cycles 1 and 2 the results of supervision have not achieved the desired targets such as guidance, the implementation of innovative learning, learning media, the suitable method, a systematic assessment of all phases of the learning process . Principal Supervision on instructional of Civics teacher in the third cycle is very good based on the results of the supervision recapitulation with the ideal score achievement with quantitative assessment with figures 91.62 which are categorized very well. It was clearly see that an increase in the performance of teachers and curriculum officers of coordinating worked. The students are better prepared to face the teaching and learning process. Individual meetings in the third cycle were meeting, conversation, dialogue, and brainstorming between the principal or supervisor, the teacher and his colleagues, and also teachers' professional skills.